Opioid and the usage in chronic non cancer pain - Simbolon, Boyke Marthin (Jurnal Prima Medika Sains, 2023)
The use of opioid in various guidelines for chronic non-cancer pain is controversial because evidence of their long-term benefits is weak. The potential for serious adverse effects and local regulations warrant caution in both prescribers and users. However, opioids have a role in the management of chronic non-cancer pain in carefully selected patients with regular monitoring and as a part of multimodal therapy. Common adverse effects should be treated promptly to improve patient compliance. We believe that opioid therapy at low doses is beneficial in some patients. It should not be denied but carefully considered on a case-by-case basis.